PENGARUH PERILAKU KARYAWAN BAGIAN DARI ORGANISASI, KELELAHAN, DAN KETERIKATAN KARYAWAN TERHADAP PRODUKTIVITAS KARYAWAN PT. THIESS CONTRACTORS INDONESIA MELAK MINE PROJECT - Suyanto, Suyanto; Ravi, Eko Ravi Pratama; Cindy Josea, Bella (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
This research aims to determine the influence of employee behavior as part of the organization, fatigue and employee engagement on employee productivity at PT. Thiess Contractors Indonesia Melak Mine Project simultaneously and partially. The research method used in this research is quantitative with a descriptive approach to the entire research object. The total sample size was 70 employees out of 1387 which was adapted by Yount's (1999) theory with a percentage of 5%. The data analysis techniques in this research are Instrument Test, Classical Assumption Test, Multiple Linear Regression, and Hypothesis Testing with the help of IBM SPSS 25 software. The research results show that employee behavior as part of the organization, fatigue and employee engagement have a significant simultaneous effect on employee productivity (p value=0.000). The variables employee behavior as part of the organization (p value=0.014) and employee engagement (p value=0.000) partially have a significant effect on employee productivity. Meanwhile, the Fatigue variable has no significant effect on employee productivity (p value=0.793).Assumption Test, Multiple Linear Regression, and Hypothesis Testing with the help of IBM SPSS 25 software. The research results show that employee behavior as part of the organization, fatigue and employee engagement have a significant simultaneous effect on employee productivity (p value=0.000). The variables employee behavior as part of the organization (p value=0.014) and employee engagement (p value=0.000) partially have a significant effect on employee productivity. Meanwhile, the Fatigue variable has no significant effect on employee productivity (p value=0.793).